KEWIRAUSAHAAN DAN USAHA MIKRO KECIL MENENGAH (UMKM) SEBAGAI SALAH SATU SOLUSI UNTUK MENGATASI MASALAH KETENAGAKERJAAN DI INDONESIA - Rizwan Aryadi; Siti Hajati Hoesin (Program Magister Ilmu Hukum Universitas Pancasila, 2022)
The crucial problems facing the government today are the problems of poverty, unemployment and income equality. One of the difficult problems that are often faced by governments in various countries is the provision of job opportunities for their residents. In response to this, the real responsibility lies with ourselves, If we can create one more job seat, at least the level of competition for employment will be slightly reduced. Unemployment also concerns dimensions of a socio-cultural nature. The low mental attitude/spirit of independence is also closely related to the problem of unemployment. This research will examine ENTREPRENEURSHIP AND MICRO, SMALL AND MEDIUM ENTERPRISES (MSMES) AS ONE OF THE SOLUTIONS TO OVERCOME EMPLOYMENT PROBLEMS IN INDONESIA. The formulation of the problem in this paper is: What is the role of entrepreneurs and MSMEs in helping to expand employment opportunities? How is the Government’s efforts in supporting Entrepreneurs and MSMEs?. Entrepreneurship and Micro, Small and Medium Enterprises (MSMEs) as well as the contribution given as a manifestation of Entrepreneurship is one of the alternative solutions to solve the problem of unemployment and employment that plagues the Indonesian nation. The role of the government is also very influential in increasing the creation of entrepreneurs and MSMEs through several supporting programs that can facilitate entrepreneurial and MSME activities